Design and testing of a high performance liquid phase cold storage system for liquid air energy storage. (15th December 2020) - An, Baolin; Chen, Jiaxiang; Deng, Zhang; Zhang, Tao; Wang, Junjie; Yang, Luwei; Chang, Xinjie
Highlights: A novel liquid air energy storage system is firstly established. Test result with liquid phase cold storage subsystem is originally obtained. The highest cold storage efficiency for the liquid air energy storage system is achieved. The method for the cold storage subsystem design is analyzed and carried out. Abstract: Liquid air energy storage is a promising large-scale energy storage technology for power grid peak-load shifting and reducing the volatility of renewable energy power generation. A high-efficiency cold storage subsystem of the liquid air energy storage system is important to guarantee good overall system performance. Liquid phase cold storage technology can avoid the heat conduction in the axial direction of that in the solid-phase media, which theoretically can achieve a higher cold storage efficiency. In this paper, the design method for liquid phase cold storage was proposed. A novel liquid air energy storage system with the compression power of 100 kW was built. The variation rules of the working medium temperatures, pressures and other key experimental results during the process of cold storage and release were tested. Results showed that the system achieved a 91.35% cold storage efficiency, providing an important basis for the liquid–air energy storage system to making it possible to gain a net round trip electricity to electricity efficiency to 50%. Methods to further improve the cold storage efficiency were also proposed in this paper.